2014
DOI: 10.1093/aob/mcu050
|View full text |Cite
|
Sign up to set email alerts
|

The first complete chloroplast genome of the Genistoid legume Lupinus luteus: evidence for a novel major lineage-specific rearrangement and new insights regarding plastome evolution in the legume family

Abstract: This study resulted in the discovery of a novel, major 36-kb inversion, specific to the Genistoids. Chloroplast mutational hotspots were also identified, which contain novel and potentially informative regions for molecular evolutionary studies at various taxonomic levels in the legumes. Taken together, the results provide new insights into the evolutionary landscape of the legume plastome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 77 publications
13
116
1
3
Order By: Relevance
“…The concatenated protein set was aligned in KAlign () and the alignment subsequently analyzed using MrBayes (Huelsenbeck and Ronquist, 2001; Ronquist and Huelsenbeck, 2003) in the Genious platform. As expected, C. canadensis was the most closely related species to T. esculentum , with the other species following the previously determined pattern of relationships (Martin et al , 2014) in this analysis.…”
Section: Resultssupporting
confidence: 84%
“…The concatenated protein set was aligned in KAlign () and the alignment subsequently analyzed using MrBayes (Huelsenbeck and Ronquist, 2001; Ronquist and Huelsenbeck, 2003) in the Genious platform. As expected, C. canadensis was the most closely related species to T. esculentum , with the other species following the previously determined pattern of relationships (Martin et al , 2014) in this analysis.…”
Section: Resultssupporting
confidence: 84%
“…Molecular analysis suggested the transfer of rpl22 gene to nucleus from the cp genome, as a functional copy of this gene has been found from the nuclear genome of P. sativum (Gantt et al, 1991). Also a functional copy of rpl22 gene was verified in the nucleus of lupine species (Martin et al, 2014). The gene infA has been lost from cp genome to nucleus in the course of angiosperm evolution in almost all rosids (Millen et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Also it is now believed that loss of IR made the chloroplast genome more prone to rearrangements, like a 50 kb inversion reported in mung bean (Palmer and Thompson, 1982), is present in most members of the papilionoideae subfamily which changes the gene order between trnK and accD genes in the LSC region (Palmer et al, 1988). Another inversion encompassing a 78 kb region in LSC was first reported in Phaseolus and Vigna , a member of subtribe phaseolinae and tribe phaseoleae (Bruneau et al, 1990; Guo et al, 2007; Tangphatsornruang et al, 2010) and a newly reported 36 kb inversion within the 50 kb inversion present in lupines and other genisotoids (Martin et al, 2014). There seems to be variation in the legumes for the presence of certain genes.…”
Section: Introductionmentioning
confidence: 89%
“…Gene rps19 is nearest to the LSC-IR boundary: in some species, like I. pubescens , H. himalaica , and Panax ginseng 21, it spans the boundary, in others, like Millettia pinnata 25 and Lupinus luteus 26, it does not extend into the IR, while in others, like Phaseolus vulgaris 27, Vigna radiata 28 and Vigna unguiculata (JQ755301 in GenBank), the whole gene is inside the IR. Gene ycf1 , nearest to the SSC-IR boundary, is similar.…”
Section: Discussionmentioning
confidence: 99%